Malarial Retinopathy: Falci Not So Fan-See! - Yogya Reddy; Reshma Ramakrishnan; Anamika Pandey; Ayushi ojha; Purva deore; Priyanka Gandhi (Delhi Journal of Ophthalmology)
Malarial retinopathy is an established entity in cases of complicated falciparum malaria and cerebral malaria in children whereas, in adults it is rarely reported. Here we report a case of a 21-year-old male, with uncomplicated falciparum malaria, referred to the ophthalmology outpatient department with a chief complaint of sudden blurring of vision in both eyes. On examination, both eyes showed mild blurring of nasal optic disc margins with multiple intraretinal, preretinal haemorrhages, subhyaloid haemorrhage involving the macula and Roth spots, suggestive of malarial retinopathy. The patient was observed closely for spontaneous resolution and was treated systemically with anti-malarial drugs including injection artesunate and tablet doxycycline. On subsequent follow-up after 2 weeks, improvement in visual acuity with complete resolution of haemorrhages occurred. We aspire to bring to light a rare entity of malarial retinopathy and the need to not over-treat the condition.